Outcomes of community‐based hepatitis C treatment by general practitioners and nurses in Australia through remote specialist consultation. Issue 11 (28th October 2021) - Haridy, James; Iyngkaran, Guru; Nicoll, Amanda; Muller, Kate; Wilson, Mark; Wigg, Alan; Ramachandran, Jeyamani; Nelson, Renjy; Bloom, Stephen; Sasadeusz, Joseph; Watkinson, Sally; Colman, Anton; et al.
Abstract: Background: A unique model of care was adopted in Australia following introduction of universal subsidised direct‐acting antiviral (DAA) access in 2016 in order to encourage rapid scale‐up of treatment. Community‐based medical practitioners and integrated hepatitis nurses initiated DAA treatment with remote hepatitis specialist approval of the planned treatment without physical review. Aims: To evaluate outcomes of community‐based treatment of hepatitis C virus (HCV) through this remote consultation process in the first 12 months of this model of care. Methods: A retrospective chart review of patients undergoing community‐based HCV treatment from general practitioners and integrated hepatitis nurse consultants through the remote consultation model in three state jurisdictions in Australia from 1 March 2016 to 28 February 2017. Results: Sustained virological response at 12 weeks (SVR12) was confirmed in 383 (65.1%) of 588 subjects intended for treatment with a median follow‐up time of 12 months (interquartile range 9–14 months). The SVR12 test was not performed in 159 (27.0%) of 588 and 307 (52.2%) of 588 did not have liver biochemistry rechecked following treatment. Subjects who completed follow up exhibited high SVR12 rates (383/392; 97.7%). Nurse‐led treatment was associated with higher confirmation of SVR12 (73.7% vs 62.4%; P = 0.01) and liver biochemistry testing post treatment (57.5% vs 45.0%; P = 0.01). Conclusions: Community‐based management of HCV through remote specialist consultation may be an effective model of care. Failure to check SVR12, recheck liver biochemistry and appropriate surveillance in patients with cirrhosis may emerge as significant issues requiring further support, education and refinement of the model to maximise effectiveness of future elimination efforts.